THE IMPACT OF NITROGEN BALANCE AND LIQUID ORGANIC FERTILIZER FROM COW URINE ON THE GROWTH AND PRODUCTION OF PAKCOY PLANTS (Brassica Chinensis L.) IN REGOSOL SOIL - Anwar, Khairul; Alpandari, Heny; Prakoso, Tangguh; Herlina, Nia (Jurnal Agrotek Tropika, 2025)
Pakcoy plants (Brassica chinensis L.) exhibit good growth and can thrive luxuriantly in various seasons, allowing for year-round cultivation. However, their productivity remains low due to insufficient soil fertility. Nitrogen is an essential nutrient required by pakcoy, and it can be obtained from liquid organic fertilizer derived from cow urine and urea. This research aims to evaluate how pakcoy plants respond to the application of nitrogen balance and liquid organic fertilizer from cow urine in regosol soil. The study was conducted at the experimental field of the Faculty of Agriculture, Muhammadiyah University of Yogyakarta, from February 2021 to June 2021. Employing a Completely Randomized Design (CRD) with a single factor, the research comprised five treatments as follows: P1: 100% Urea 1.2 grams (control), P2: 75% Urea 0.9 grams + 25% POC Cow Urine 5 ml, P3: 50% Urea 0.6 grams + 50% POC Cow Urine 10 ml, P4: 25% Urea 0.3 grams + 75% POC Cow Urine 15 ml, P5: 100% POC Cow Urine 20 ml. Each treatment of POC Cow Urine and Nitrogen (Urea) balance was replicated four times, resulting in a total of 20 experimental units. The results showed that the application of nitrogen balance and POC cow urine significantly impacted plant height, number of leaves, leaf area, fresh weight of aboveground parts, dry weight of aboveground parts, fresh weight of roots, dry weight of roots, and root length in the treatment involving 50% Urea 0.6 grams + 50% POC Cow Urine. This indicates that the application of nitrogen balance and POC cow urine can effectively fulfill the nitrogen nutrient requirements of pakcoy plants.Keywords: Pakcoy, Nitrogen Balance, POC, Regosol